2017
DOI: 10.4012/dmj.2016-301
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity, cytotoxicity and mechanical behavior of nano-enhanced denture base resin with different kinds of inorganic antibacterial agents

Abstract: Silanized aluminum borate whiskers (ABWs) of 4 wt%, silanized zirconium dioxide nanoparticles (nano-ZrO2) of 2 wt% were mixed with polymethyl methacrylate (PMMA) powder to get ZrO2-ABWs/PMMA composites. Titanium dioxide (TiO2), silver-supported titanium dioxide (Ag/TiO2), silver-supported zirconium phosphate (Novaron) and tetrapod-like zinc oxide whiskers (T-ZnOw) antibacterial agents of 3 wt% were mixed with ZrO2-ABWs/PMMA composites respectively to fabricate standard specimens. Plaque biofilms on the specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 39 publications
1
68
1
7
Order By: Relevance
“…[ 186 ] In dentistry, TiO 2 nanoparticles have been mixed with commercial and noncommercial dental resins to produce tooth filling materials with antimicrobial properties and improved mechanical strength. [ 187,188 ] As a wide‐bandgap semiconductor, TiO 2 nanoparticles have been incorporated into antibacterial paints or coatings for hospital touch‐surfaces where their antibacterial activity may be activated by excitation with visible light. [ 189 ] Excitation of TiO 2 nanoparticles by ultraviolet light produces ROS that can destroy many organic molecules.…”
Section: Metal‐based Nanocompoundsmentioning
confidence: 99%
“…[ 186 ] In dentistry, TiO 2 nanoparticles have been mixed with commercial and noncommercial dental resins to produce tooth filling materials with antimicrobial properties and improved mechanical strength. [ 187,188 ] As a wide‐bandgap semiconductor, TiO 2 nanoparticles have been incorporated into antibacterial paints or coatings for hospital touch‐surfaces where their antibacterial activity may be activated by excitation with visible light. [ 189 ] Excitation of TiO 2 nanoparticles by ultraviolet light produces ROS that can destroy many organic molecules.…”
Section: Metal‐based Nanocompoundsmentioning
confidence: 99%
“…30,31 It has been reported that composite resin containing zirconium oxide particles and aluminum borate whisker showed higher antibacterial activity. 32 In this study, antibacterial activity was not evaluated, but it is necessary to conduct further studies to investigate the antibacterial effects of different contents of materials. The surface roughness of restorative materials has a major effect on the discoloration and initial bacterial adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the use of 3% of TiO 2 resulted in antibacterial activity without comprising the mechanical properties and cytotoxicity of PMMA [21]. Another research on the addition of TiO 2 into PMMA showed that the incorporation of nano-sized TiO 2 adversely affected the mechanical properties and the flexural strength values with increase in TiO 2 concentration [33].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al ., 2017 revealed that the use of nano-sized 3% TiO 2 had antibacterial activities compared to the control and blank groups with no significant differences in the cytotoxicity and found no significant differences in the mechanical properties compared to the control group within the range of an appropriate ratio [21]. The different percentages of superinducing TiO 2 nanofiller 1% and 5% were added to the acrylic which showed that 5% of TiO 2 nanoparticles can adversely affect its flexural strength [22].…”
Section: Introductionmentioning
confidence: 99%